Particulate matter emissions from commercial beef cattle feedlots in Kansas - Bonifacio, Henry F. (Kansas State University, 2009)
Large cattle feedlots in Kansas are often considered to be large sources of particulate matter (PM), including PM with equivalent aerodynamic diameter of 10 micrometers or less (PM[subscript]10). To control PM emissions from cattle feedlots, water sprinkler systems can be implemented; however, limited data are available on their PM control efficiency. This research was conducted to determine the control efficiency of a water sprinkler system in reducing PM[subscript]10 emission from a cattle feedlot. This was accomplished by monitoring the PM[subscript]10 concentrations, with tapered element oscillating microbalance (TEOM™) PM[subscript]10 monitors, at the upwind and downwind boundaries of a cattle feedlot (KS1) from January 2006 to July 2009. The feedlot was equipped with a sprinkler system that can apply up to 5 mm of water per day. It had approximately 30,000 head of beef cattle and total pen area of approximately 50 ha. The control efficiency of the sprinkler system was determined by considering the PM[subscript]10 data during sprinkler on/off events, i.e., the sprinkler system was operated (on) for at least one day and either followed or preceded by at least one day of no water sprinkling (off). For each of the selected sprinkler on/off events, the percentage reduction in net PM[subscript]10 concentration was calculated and considered to be a measure of the control efficiency. Net PM[subscript]10 concentration was defined as the difference between downwind and upwind PM[subscript]10 concentrations. The control efficiency for PM[subscript]10 ranged from 32% to 80%, with an overall mean of 53% based on 24-h PM[subscript]10 values for 10 sprinkler on/off events. In general, the effect of the water sprinkler system in reducing net PM[subscript]10 concentration lasted for one day or less. The percentage reduction in net PM[subscript]10 concentration at KS1 due to rainfall events was also determined using a similar approach. In addition, a second cattle feedlot (KS2) that was not equipped with a sprinkler system and with approximately 25,000 head of beef cattle and 68 ha pen area was considered. Percentage reductions in net PM[subscript]10 concentrations due to rainfall events were mostly in the range of 60% to almost 100% for both feedlots, with overall means of 75% for KS1 and 74% for KS2. The effects of rainfall events (with rainfall amounts > 10 mm/day) lasted for three to seven days, depending on rainfall amount and intensity. Limited data are also available on PM[subscript]10 emission rates from cattle feedlots in Kansas. This research quantified PM[subscript]10 emission rates from the two feedlots (KS1 and KS2) and a third cattle feedlot (KS3) in Kansas by using inverse dispersion modeling with the AMS/EPA Regulatory Model (AERMOD), which is the US EPA preferred regulatory atmospheric dispersion model. PM[subscript]10 emission rates were back-calculated using the resulting PM[subscript]10 concentrations modeled by AERMOD, together with measured PM[subscript]10 concentrations (24 months of data for KS1 and KS2, 6 months of data for KS3). Overall mean PM[subscript]10 emission fluxes for the 2-year period were 1.29 g/m[superscript]2-day (range: 0.04 – 4.98 g/m[superscript]2-day) for KS1, 1.03 g/m[superscript]2-day (range: 0.07 – 4.52 g/m[superscript]2-day) for KS2, and 2.48 g/m[superscript]2-day (6-months; range: 0.05 – 5.00 g/m[superscript]2-day) for KS3. The corresponding mean PM[subscript]10 emission factors were 21, 29, and 48 kg/1,000 hd-day for KS1, KS2, and KS3, respectively. The emission factors for KS1 and KS2 were considerably smaller than the published US EPA emission factor for cattle feedlots (i.e., 42 kg/1000 hd-day). The emission factor for KS3 was slightly greater than the US EPA emission factor; however, it was a biased estimate because it was based only on a six-month period.
Keywords: Particulate matter in cattle feedlots; Sprinkler system particulate matter control efficiency; AERMOD application for cattle feedlots; Particulate matter emission factors and fluxes for cattle feedlots; Engineering, Agricultural (0539); Engineering, Environmental (0775)